DELAYS IN THE INTERNATIONAL SEABED AUTHORITY MINING CODE: INSIGHT FROM TWAIL AND BBNJ FRAMEWORKS - Putri, Ria Wierma; Khanza, Yuga Narazua; Davey, Orima Melati; Sabatira, Febryani (UI Scholars Hub, 2024)
The International Seabed Authority (ISA) plays a crucial role in governing the vast expanses of the ocean floor that lie beyond national jurisdictions, referred to as